Association Between Triglyceride–Glucose Index and the Risk of Type 2 Diabetes Mellitus in an Older Chinese Population Aged Over 75 Years - Fu, Xiaomin; Liu, Hongzhou; Liu, Jing; Li, Nan; Li, Lele; Ke, Dianshan; Liu, Minyan; Lu, Yanhui; Duan, Lihua; Ma, Linlin; Huo, Yanfei; Lei, Qinghua; et al. (Frontiers in Public Health, 2022)
Background: The association between triglyceride-glucose (TyG) index and type 2 diabetes mellitus (T2DM) in the older adults has not been fully understood. This research aims to explore the to explore the association between de TyG index and the incidence of T2DM in an older Chinese population aged over 75 years. Methods: This longitudinal analysis study was performed based on a database from a health check screening programme in China. The participants were stratified based on the quintile ranges of TyG index (Q1 to Q5 groups). T2DM was defined as fasting plasma glucose > = 7.00 mmol/L and/or self-reported T2DM. The cumulative incidences of T2DM in various quintile groups were estimated by the Kaplan-Meier method. The Cox proportional hazard model was used to examine the independent impact of TyG index on the risk of T2DM during the follow up period. Subgroup analysis was performed by gender and BMI to further validate the credibility of the results. Results: During the follow up period, a total of 231 new-onset T2DM cases were recorded among the 2,571 individuals aged over 75 years. After adjusting confounding factors, elevated TyG index independently indicated a higher risk of T2DM (HR = 1.89; 95% CI, 1.47 - 2.44; P < 0.01). Higher TyG index quintile groups (Q3 to Q5) also presented with higher risk of T2DM (hazard ratio (HR) = 1.36, 1.44 and 2.12, respectively) as compared with the lowest quintile group (Q1). Subgroup analysis showed that increased TyG index led to an higher risk of T2DM with HR = 2.35 (95% CI, 1.73 - 3.19), 1.90 (95% CI, 1.27 - 2.83), 2.95 (95% CI, 1.94 - 4.50) and 1.72 (95% CI, 1.25 - 2.35) in male subgroup, female subgroup, BMI < 24 kg/m2 subgroup and BMI >= 24 kg/m2 subgroup, respectively. Conclusions: TyG index is independently correlated with the risk of incident T2DM in Chinese adults aged over 75 years. TyG index might be useful in monitoring T2DM in the elder populations.